Kabbalah : the mystic quest in Judaism - Ariel, David S. (Lanham, Md. : Rowman & Littlefield, 2006)
In the wake of the renewed interest in Kabbalah comes a thoroughly updated edition of Ariel's classic best selling book, "The Mystic Quest." Ariel beautifully presents the complex elements of Jewish mysticism's major ideas in clear, understandable, and accessible language.
Seekers of unity : the nature of mysticism -- Visionaries, mystics, and kabbalists : the history of Jewish mysticism -- The hidden and the revealed : the infinite God of Jewish mysticism -- The calculus of the divine world : the teaching of the sefirot -- The shekhinah : the feminine aspect of God -- Entering the garden : the meaning of Torah -- The oneness of being : the destiny of the soul -- The mystic drama : the religious life of the Jewish mystic -- Raising the sparks : modern Jewish mysticism -- Mysticism and meditation : the mystic quest.
Includes bibliographical references (pages 235-239) and index.
Description based on print version record.
Keywords: Mysticism -- Judaism; Cabala; Kabbala; Kabbala; Cabala; Mysticism -- Judaism; RELIGION / Judaism / General; Electronic books